Optimising Use of Cultural Heritage - Christian Koboldt (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 1995)
The paper gives a working definition of "cultural heritage" as collection of tangible objects related to the cultural development of a society that are inherited from past generations and are valued by contemporaries as an expression of this cultural development. The potential benefits and costs of using this assets are discussed briefly. The main focus is on analysing how the institutional arrangements under whisch specific parts of the cultural heritage are made available to potential users affect the welfare created by the use of these assets. This allows to draw some conclusions about the optimal way of using cultural heritage. – – Der Beitrag gibt zunächst eine Arbeitsdefinition für "kulturelles Erbe" als eine Sammlung von Objekten und Artefakten, die mit der kulturellen Entwicklung einer Gesellschaft in Beziehung stehen, von vergangenen Generationen hinterlassen und von Zeitgenossen als Ausdruck dieser kulturellen Entwicklung geschätzt werden. Nutzen und Kosten der Nutzung des kulturellen Erbes werden kurz diskutiert. Hauptanliegen des Beitrages ist eine Analyse der Auswirkungen unterschiedlicher institutioneller Arrangements der Nutzung auf die mit der Nutzung realisierbare Wohlfahrt. Aus dieser Analyse lassen sich Schlußfolgerungen für die optimale Nutzung von Objekten des kulturellen Erbes ziehen.
Keywords: K41; 330; Litigation fees; opportunistic suits; positive detection skill; Kulturgut; Kulturökonomik; Kosten-Nutzen-Analyse; Wohlfahrtstheorie; Theorie